Der Aufbau der ostdeutschen Infrastruktur und sein Beitrag zur wirtschaftlichen Entwicklung in Sachsen - Klaus-Heiner Röhl (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2000)
This discussion paper deals with the reconstruction of transportation and telecommunication infrastructures in Eastern Germany and especially Saxony after the 1990 unification. Following a representation of investment measures and their influence on capital stocks in transportation infrastructure the author discusses the infrastructural situation of Saxony's three main agglomerations Dresden, Leipzig, Chemnitz and their location in European economic space. Concluding the paper Saxony's integration into the system of "Transeuropean Networks" and their planned extensions into Central and Eastern Europe is briefly examined.
Keywords: 330; Verkehrsinvestition; Verkehrsinfrastrukturpolitik; Verkehrserschließung; Standortfaktor; Sachsen